Diabetes mellitus and candidiases - Dorko, E; Baranová, Z; Jenca, A; Kizek, P; Pilipcinec, E; Tkáciková, L (Folia microbiologica, 2005)
Patients in various clinical states of diabetes mellitus (according to the recommendation of the American Diabetes Association) as a primary diagnosis were examined for fungal infections by Candida species. Candida spp. were detected in urine, in the material taken from the mouth cavity, nails, skin lesions, ears and eyes, by cultivation on the Sabouraud agar, CHROMagar Candida, and by saccharide assimilation. In the group of diabetics with symptoms of oral candidiasis and denture stomatitis C. albicans was identified in 8 cases, C. tropicalis in 3, C. parapsilosis in 2; 1 strain of C. guilliermondii was also isolated. In patients with urinary tract infections the presence of C. albicans was shown in 12 cases; C. parapsilosis was detected in 6 cases and two strains of each C. tropicalis and C. krusei were also isolated. In patients with leg ulcers C. albicans (25 cases), C. parapsilosis (5), C. tropicalis (3) and one strain of each C. krusei and C. robusta were isolated. Otomycosis was associated with one strain of C. albicans, C. parapsilosis, C. tropicalis and C. guilliermondii. C. albicans was most frequently associated with onychomycosis, paronychia and endophthalmitis; C. parapsilosis was the second most rated yeast.
Keywords: Diabetes Mellitus; Candidiasis, Oral; orální kandidóza; retrospektivní studie; Humans; kandidóza; Candidiasis; diabetes mellitus; lidé; kandidóza kožní; komplikace diabetu; Retrospective Studies; Diabetes Complications; Candidiasis, Cutaneous; Candida